WORLD OF TARAS SHEVCHENKO PAINTING (to 200 anniversary of birth of Ukrainian genius) - Макаровський, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The bases of art-esthetic T. Shevchenko view are reproduced in the article, the national lines of his painting are analysed and specified.